Preparation method of annular neodymium-iron-boron magnet
By using modified lubricants and composite adhesives in the preparation process of NdFeB magnets, the problem of poor magnet density and magnetic performance in traditional methods is solved, and a circular ring type NdFeB with high density and excellent magnetic properties is achieved Magnets expand their application range.
Patent Information
- Application Number
- CN202411497937.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The traditional NdFeB magnet preparation method has problems such as cumbersome processing steps, low accuracy and environmental pollution, resulting in poor magnet density and magnetic performance, limiting its application in a wider range of fields.
In the preparation process of NdFeB magnets, uniformly distributed and closely arranged magnet powder is formed through smelting, hydrogen crushing, airflow grinding, pressing, sintering and other steps to improve the density and magnetic properties of the magnets. able.
The circular neodymium iron boron magnet with high density and excellent magnetic properties reduces the agglomeration of powder particles, forms a highly ordered magnetic domain structure, and improves the performance and density of the magnet.
Smart Images

Figure BDA0005101765880000031 
Figure BDA0005101765880000051 
Figure BDA0005101765880000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of NdFeB magnets, and in particular relates to a method for preparing a ring-shaped NdFeB magnet. Background Art
[0002] With the rapid development of science and technology, NdFeB permanent magnet materials are increasingly widely used in military equipment, new energy vehicle motors, high-end intelligent robots and other fields due to their high magnetic energy product, high coercive force and good mechanical properties. Especially in the field of new energy vehicles, with the continuous expansion of the electric vehicle market, the demand for high-performance permanent magnet materials has increased dramatically. Ring-shaped NdFeB magnets have become key materials in motor manufacturing due to their unique shape and excellent magnetic properties. However, the traditional preparation method of NdFeB magnets has problems such as cumbersome processing procedures, low processing accuracy and environmental pollution. These problems not only affect the performance of the magnet, but also increase the production cost, limiting its application in a wider range of fields. Therefore, the preparation method of high-performance ring-shaped NdFeB magnets is particularly important.
[0003] Patent CN 111968817 A discloses a method for preparing a toroidal NdFeB magnet, including hydrogen crushing the raw material; adding a compound lubricant to the hydrogen crushed powder, stirring and mixing evenly, and then jet milling the powder to obtain fine powder; adding a compound lubricant and nano copper powder to the fine powder, stirring and mixing evenly; pouring the obtained material into a mold cavity, pressing and molding to obtain a green embryo; taking out the green embryo together with the column core, evacuating and packaging with a vacuum packaging machine, and then isostatic pressing; finally taking out the column core, putting the green embryo into a sintering material box and putting it into a sintering furnace for high-temperature sintering and two aging treatments. The lubricant added in the invention will not leave too many impurities in the magnet, but the density of the obtained magnet and the magnetic properties of the magnet still have room for improvement. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a ring-shaped NdFeB magnet, so as to solve the technical problems of poor magnet density and magnetic properties in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing a ring-shaped NdFeB magnet, comprising the following steps:
[0007] Step 1: Mixing NdFeB magnet raw materials, modified lubricant and distilled water, smelting, hydrogen crushing and jet milling to obtain NdFeB magnet powder with uniform particle size distribution;
[0008] Step 2: Mix the NdFeB magnet powder with the composite binder, stir, put into a mold, and press the powder into a ring-shaped green body;
[0009] Step 3: placing the annular green body into a sintering furnace and sintering at high temperature to obtain a magnet;
[0010] Step 4: Grind, cut and nickel-plate the magnet to obtain a ring-shaped NdFeB magnet.
[0011] Preferably, in step 1, the dosage ratio of the NdFeB magnet raw material, the modified lubricant and distilled water is (1-3) kg: (20-25) g: (200-280) mL, and the mixing time is 4-5 h.
[0012] Preferably, the method for preparing the modified lubricant comprises the following steps:
[0013] Q1: Add 3-nitro-1,8-naphthalene dicarboxylic anhydride to a container containing anhydrous ethanol, then add N,N-dimethylethylenediamine and ethanol solution, and heat the reaction in an oil bath under nitrogen protection. After the reaction is completed, cool with ice water, filter under reduced pressure, wash, and dry to obtain intermediate 1;
[0014] Q2: Add the intermediate product 1 to a container containing anhydrous ethanol, then add triethylamine and palladium carbon, heat under reflux and stir under nitrogen protection, then add formic acid dropwise into the container through a syringe to initiate the reaction, filter after the reaction, cool the filtrate in ice water, filter under reduced pressure, wash, and dry to obtain the intermediate product 2;
[0015] Q3: The intermediate product 2, toluene, 2-methylbenzaldehyde and diethyl phosphite are added into the container in sequence, and refluxed with stirring under nitrogen protection. After the reflux is completed, the mixture is evaporated under reduced pressure, redissolved and purified to obtain a modified lubricant.
[0016] In the above process, the synthetic reaction formula of the modified lubricant is as follows:
[0017]
[0018] The results of mass spectrometry analysis of intermediate product 1 are: m / z: 313.11 (100.0%), 314.11 (17.6%), 315.11 (2.4%), 314.10 (1.1%); the results of mass spectrometry analysis of intermediate product 2 are: m / z: 283.13 (100.0%), 284.14 (17.6%), 285.14 (1.9%), 284.13 (1.1%); the results of mass spectrometry analysis of modified lubricant are: m / z: 523.22 (100.0%), 524.23 (30.9%), 525.23 (5.6%), 524.22 (1.1%).
[0019] Preferably, in Q1, the dosage ratio of 3-nitro-1,8-naphthalene dicarboxylic anhydride, anhydrous ethanol, N,N-dimethylethylenediamine and ethanol solution is (3.66-6.22) g: (100-170) mL: (1.32-2.24) g: (45-76.5) mL, the volume fraction of the ethanol solution is 70vt%, the oil bath heating reaction temperature is 70-80°C, the time is 2-4h, and the reaction is washed 3-5 times with n-heptane.
[0020] Preferably, in Q2, the dosage ratio of the intermediate product 1, anhydrous ethanol, triethylamine, palladium carbon and formic acid is (4-6) g: (40-60) mL: (2.3-3.45) mL: (0.4-0.6) g: (1-1.5) mL, the heating reflux stirring temperature is 70-90°C, the time is 6-8h, filtered with diatomaceous earth, and washed with n-heptane 3-5 times.
[0021] Preferably, in Q3, the amount ratio of the intermediate product 2, toluene, 2-methylbenzaldehyde and diethyl phosphite is (0.28-0.56) g: (25-50) mL: (1.2-2.4) g: (0.14-0.28) g, the stirring reflux time is 10-12 h, redissolved with dichloromethane, and purified using a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 4:1 as an eluent.
[0022] Preferably, in step 2, the ratio of NdFeB magnet powder to composite binder is (1-3) kg: (200-250) g, and the mold used is a circular ring mold.
[0023] Preferably, the method for preparing the composite binder comprises the following steps:
[0024] S1: Add phenolphthalein monomer to a container containing acetic acid, stir to dissolve, then add yttrium nitrate hexahydrate, stir vigorously, pour into a container filled with low-temperature deionized water, wash, filter, and dry to obtain dinitrophenolphthalein; add dinitrophenolphthalein to a container containing tetrahydrofuran, stir, add anhydrous ethanol and palladium carbon, evacuate, heat to react, filter after the reaction is completed, heat, cool, filter, and dry to obtain diaminophenolphthalein;
[0025] S2: Add diaminophenolphthalein to a container, then add N-methylpyrrolidone, stir until completely dissolved under a nitrogen atmosphere, then place in an ice-water environment, add hexafluorodianhydride in portions, stir to react, and obtain a mucus; remove the ice-water bath, add toluene to the mucus, mix well, connect a water separator and a condenser to the container, heat to react, cool naturally, and crush, filter, wash, and dry the obtained precipitate to obtain a powder;
[0026] S3: The powder is mixed with polyacrylamide and dissolved in dimethyl sulfoxide, and then azobisisobutyronitrile is added, and heated to react to obtain a composite adhesive.
[0027] In the above process, the synthetic reaction formula of the powder is as follows:
[0028]
[0029] The results of mass spectrometry analysis of dinitrophenolphthalein were: m / z: 408.06 (100.0%), 409.06 (22.7%), 410.07 (2.3%), 410.06 (1.8%); the results of mass spectrometry analysis of diaminophenolphthalein were: m / z: 348.11 (100.0%), 349.11 (22.4%), 350.12 (3.1%).
[0030] Preferably, in S1, the amount ratio of phenolphthalein monomer, acetic acid and yttrium nitrate hexahydrate is (2-4) g: (60-120) mL: (2.4-4.8) g, and the vigorous stirring time is 1-2 h; the amount ratio of dinitrophenolphthalein, tetrahydrofuran, anhydrous ethanol and palladium carbon is (5-10) g: (30-60) mL: (20-40) mL: (0.5-1) g, the stirring time is 20-30 min, the heating reaction temperature is 60-70 ° C, the time is 10-12 h, the cooling temperature is 3-6 ° C, and the time is 10-14 h; in S2, diaminophenolphthalein, N-methyl The dosage ratio of pyrrolidone and hexafluorodianhydride is (4.2-8.4) g: (15-30) mL: (5.3-10.6) g, the stirring time is 30-45 min, the time in the ice water environment is 0-3°C, the time interval for adding hexafluorodianhydride is 20-25 min, and the stirring reaction time is 20-24 h; the dosage ratio of mucus and toluene is (20-22) mL: (15-18) mL, the heating reaction temperature is 160-180°C, the time is 6-8 h, and the drying process is: keep warm at 60°C for 24 h, keep warm at 90°C for 12 h, keep warm at 120°C for 12 h, and keep warm at 150°C for 24 h.
[0031] Preferably, in S3, the ratio of the powder, polyacrylamide, dimethyl sulfoxide and azobisisobutyronitrile is (7-12) g: (6-10) g: (5-10) mL: (0.05-0.08) g, the heating reaction temperature is 70-80° C., and the reaction time is 5-7 h.
[0032] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0033] The invention firstly uses 3-nitro-1,8-naphthalic anhydride, N,N-dimethylethylenediamine, 2-methylbenzaldehyde and diethyl phosphite as raw materials to prepare a modified lubricant, and then uses phenolphthalein monomer, hexafluorodianhydride and polyacrylamide as raw materials to prepare a composite binder. In the preparation process of the annular NdFeB magnet, the addition of the modified lubricant can form a lubricating layer between powder particles, reduce the friction between particles, thereby helping the powder particles to be evenly distributed and closely arranged during the pressing and sintering process, and also prevent the agglomeration of the powder particles, so that the powder particles are kept in a dispersed state, thereby forming a highly ordered magnetic domain structure; and the addition of the composite binder helps the orientation of the magnet powder particles in the magnetic field, so that more magnetic moments are arranged along the direction of the magnetic field, thereby improving the performance of the magnet, and the interface effect generated between the composite binder and the magnet raw material can promote the arrangement of the magnet and improve the magnetic properties, and at the same time, the composite binder can be filled into the gaps between the magnet powder particles, so that the porosity is reduced during the pressing and sintering process, thereby improving the density of the magnet. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1: This example discloses a method for preparing a modified lubricant, comprising the following steps:
[0036] Q1: 4.94 g of 3-nitro-1,8-naphthalene dicarboxylic anhydride was added to a container containing 135 mL of anhydrous ethanol, followed by the addition of 1.78 g of N,N-dimethylethylenediamine and 60.75 mL of a 70% by volume ethanol solution. The mixture was heated in an oil bath at 80°C for 4 h under nitrogen protection. After the reaction was completed, the mixture was cooled with ice water, filtered under reduced pressure, washed with n-heptane for 3 times, and dried to obtain an intermediate product 1.
[0037] Q2: 5 g of intermediate product 1 was added to a container containing 50 mL of anhydrous ethanol, followed by 2.85 mL of triethylamine and 0.5 g of palladium carbon. Under nitrogen protection, the mixture was heated at 80 °C for reflux with stirring for 8 h. Then, 1.25 mL of formic acid was added dropwise to the container through a syringe to initiate the reaction. After the reaction was completed, the mixture was filtered with diatomaceous earth, the filtrate was cooled in ice water, filtered under reduced pressure, washed 3 times with n-heptane, and dried to obtain intermediate product 2;
[0038] Q3: 0.42 g of intermediate product 2, 35.5 mL of toluene, 1.8 g of 2-methylbenzaldehyde and 0.21 g of diethyl phosphite were added to the container in sequence. Under nitrogen protection, the mixture was stirred and refluxed for 12 h. After the reflux, the mixture was evaporated under reduced pressure and redissolved with dichloromethane. A mixed solution of ethyl acetate and petroleum ether in a volume ratio of 4:1 was used as an eluent for purification to obtain a modified lubricant.
[0039] This embodiment discloses a method for preparing a composite adhesive, comprising the following steps:
[0040] S1: Add 3g of phenolphthalein monomer to a container containing 90mL of acetic acid, stir to dissolve, then add 3.6g of yttrium nitrate hexahydrate, stir vigorously for 2h, pour into a container filled with low-temperature deionized water, wash, filter, and dry to obtain dinitrophenolphthalein; add 7.5g of dinitrophenolphthalein to a container containing 45mL of tetrahydrofuran, stir for 30min, add 30mL of anhydrous ethanol and 0.75g of palladium carbon, evacuate, heat at 70°C for reaction for 12h, filter after the reaction, heat, cool at 6°C for 10h, filter, and dry to obtain diaminophenolphthalein;
[0041] S2: Add 6.3 g of diaminophenolphthalein to a container, then add 25 mL of N-methylpyrrolidone, stir for 45 min under a nitrogen atmosphere until completely dissolved, then place in an ice water environment at 0°C, add a total of 7.95 g of hexafluorodianhydride three times on average, add once every 20 min, stir and react for 24 h to obtain mucus; remove the ice water bath, add 16.5 mL of toluene to 21 mL of mucus, mix well, connect the water separator and the condenser to the container, heat at 180°C for 8 h, cool naturally, crush, filter, wash and dry the obtained precipitate, and the drying process is: keep warm at 60°C for 24 h, keep warm at 90°C for 12 h, keep warm at 120°C for 12 h, and keep warm at 150°C for 24 h to obtain powder;
[0042] S3: 9.5 g of the powder was mixed with 8 g of polyacrylamide and dissolved in 7.5 mL of dimethyl sulfoxide. Then 0.065 g of azobisisobutyronitrile was added and heated at 80° C. for 6 h to obtain a composite adhesive.
[0043] This embodiment discloses a method for preparing a ring-shaped NdFeB magnet, comprising the following steps:
[0044] Step 1: 2 kg of NdFeB magnet raw material, 22.5 g of modified lubricant and 240 mL of distilled water were mixed for 5 hours, smelted, hydrogen crushed and jet milled to obtain NdFeB magnet powder with uniform particle size distribution;
[0045] Step 2: Mix 2kg of NdFeB magnet powder with 225g of composite binder, stir, put into a ring-shaped mold, and press the powder into a ring-shaped green body;
[0046] Step 3: placing the annular green body into a sintering furnace and sintering at high temperature to obtain a magnet;
[0047] Step 4: Grind, cut and nickel-plate the magnet to obtain a ring-shaped NdFeB magnet.
[0048] Example 2: This example discloses a method for preparing a modified lubricant, comprising the following steps:
[0049] Q1: 3.66 g of 3-nitro-1,8-naphthalene dicarboxylic anhydride was added to a container containing 170 mL of anhydrous ethanol, followed by 1.32 g of N,N-dimethylethylenediamine and 45 mL of 70% by volume ethanol solution. The mixture was heated in an oil bath at 80°C for 4 h under nitrogen protection. After the reaction was completed, the mixture was cooled with ice water, filtered under reduced pressure, washed with n-heptane for 3 times, and dried to obtain intermediate 1.
[0050] Q2: 4 g of intermediate product 1 was added to a container containing 60 mL of anhydrous ethanol, followed by 2.3 mL of triethylamine and 0.4 g of palladium carbon. Under nitrogen protection, the mixture was heated at 80°C for reflux with stirring for 8 h. Then, 1.5 mL of formic acid was added dropwise to the container through a syringe to initiate the reaction. After the reaction was completed, the mixture was filtered with diatomaceous earth, the filtrate was cooled in ice water, filtered under reduced pressure, washed 3 times with n-heptane, and dried to obtain intermediate product 2;
[0051] Q3: 0.28 g of intermediate product 2, 25 mL of toluene, 2.4 g of 2-methylbenzaldehyde and 0.28 g of diethyl phosphite were added to the container in sequence. Under nitrogen protection, the mixture was stirred and refluxed for 12 h. After the reflux, the mixture was evaporated under reduced pressure and redissolved with dichloromethane. A mixed solution of ethyl acetate and petroleum ether in a volume ratio of 4:1 was used as an eluent for purification to obtain a modified lubricant.
[0052] This embodiment discloses a method for preparing a composite adhesive, comprising the following steps:
[0053] S1: Add 2 g of phenolphthalein monomer to a container containing 120 mL of acetic acid, stir to dissolve, then add 2.4 g of yttrium nitrate hexahydrate, stir vigorously for 2 h, pour into a container filled with low-temperature deionized water, wash, filter, and dry to obtain dinitrophenolphthalein; add 10 g of dinitrophenolphthalein to a container containing 30 mL of tetrahydrofuran, stir for 30 min, add 40 mL of anhydrous ethanol and 1 g of palladium carbon, evacuate, heat at 70 ° C for 12 h, filter after the reaction, heat, cool at 6 ° C for 10 h, filter, and dry to obtain diaminophenolphthalein;
[0054] S2: Add 4.2g of diaminophenolphthalein to a container, then add 15mL of N-methylpyrrolidone, stir for 45min under nitrogen atmosphere until completely dissolved, then place in an ice water environment at 0°C, add a total of 5.3g of hexafluorodianhydride three times on average, add once every 20min, stir and react for 24h to obtain mucus; remove the ice water bath, add 15mL of toluene to 20mL of mucus, mix well, connect the water separator and condenser to the container, heat at 180°C for 8h, cool naturally, crush, filter, wash and dry the obtained precipitate, and the drying process is: keep warm at 60°C for 24h, keep warm at 90°C for 12h, keep warm at 120°C for 12h, and keep warm at 150°C for 24h to obtain powder;
[0055] S3: 7 g of the powder was mixed with 6 g of polyacrylamide and dissolved in 5 mL of dimethyl sulfoxide. Then 0.05 g of azobisisobutyronitrile was added and heated at 80° C. for 6 h to obtain a composite adhesive.
[0056] This embodiment discloses a method for preparing a ring-shaped NdFeB magnet, comprising the following steps:
[0057] Step 1: Mix 1 kg of NdFeB magnet raw material, 20 g of modified lubricant and 280 mL of distilled water for 5 hours, smelt, hydrogen crush and jet mill to obtain NdFeB magnet powder with uniform particle size distribution;
[0058] Step 2: Mix 1 kg of NdFeB magnet powder with 200 g of composite binder, stir, put into a ring-shaped mold, and press the powder into a ring-shaped green body;
[0059] Step 3: placing the annular green body into a sintering furnace and sintering at high temperature to obtain a magnet;
[0060] Step 4: Grind, cut and nickel-plate the magnet to obtain a ring-shaped NdFeB magnet.
[0061] Example 3: This example discloses a method for preparing a modified lubricant, comprising the following steps:
[0062] Q1: Add 6.22 g of 3-nitro-1,8-naphthalene dicarboxylic anhydride to a container containing 100 mL of anhydrous ethanol, then add 2.24 g of N,N-dimethylethylenediamine and 76.5 mL of 70% by volume ethanol solution, and heat in an oil bath at 80°C for 4 h under nitrogen protection. After the reaction is completed, cool with ice water, filter under reduced pressure, wash with n-heptane 3 times, and dry to obtain intermediate 1;
[0063] Q2: 6 g of intermediate product 1 was added to a container containing 40 mL of anhydrous ethanol, followed by 3.45 mL of triethylamine and 0.6 g of palladium carbon. Under nitrogen protection, the mixture was heated at 80 °C for reflux with stirring for 8 h. Then, 1 mL of formic acid was added dropwise to the container through a syringe to initiate the reaction. After the reaction was completed, the mixture was filtered with diatomaceous earth, the filtrate was cooled in ice water, filtered under reduced pressure, washed 3 times with n-heptane, and dried to obtain intermediate product 2;
[0064] Q3: 0.56 g of intermediate product 2, 50 mL of toluene, 1.2 g of 2-methylbenzaldehyde and 0.14 g of diethyl phosphite were added to the container in sequence. Under nitrogen protection, the mixture was stirred and refluxed for 12 h. After the reflux, the mixture was evaporated under reduced pressure and redissolved with dichloromethane. A mixed solution of ethyl acetate and petroleum ether in a volume ratio of 4:1 was used as an eluent for purification to obtain a modified lubricant.
[0065] This embodiment discloses a method for preparing a composite adhesive, comprising the following steps:
[0066] S1: Add 4 g of phenolphthalein monomer to a container containing 60 mL of acetic acid, stir to dissolve, then add 4.8 g of yttrium nitrate hexahydrate, stir vigorously for 2 h, pour into a container filled with low-temperature deionized water, wash, filter, and dry to obtain dinitrophenolphthalein; add 5 g of dinitrophenolphthalein to a container containing 60 mL of tetrahydrofuran, stir for 30 min, add 20 mL of anhydrous ethanol and 0.5 g of palladium carbon, evacuate, heat at 70°C for reaction for 12 h, filter after the reaction, heat, cool at 6°C for 10 h, filter, and dry to obtain diaminophenolphthalein;
[0067] S2: Add 8.4 g of diaminophenolphthalein to a container, then add 30 mL of N-methylpyrrolidone, stir for 45 min under a nitrogen atmosphere until completely dissolved, then place in an ice water environment at 0°C, add a total of 10.6 g of hexafluorodianhydride three times on average, add once every 20 min, stir and react for 24 h to obtain mucus; remove the ice water bath, add 18 mL of toluene to 22 mL of mucus, mix well, connect the water separator and the condenser to the container, heat at 180°C for 8 h, cool naturally, crush, filter, wash and dry the obtained precipitate, and the drying process is: keep warm at 60°C for 24 h, keep warm at 90°C for 12 h, keep warm at 120°C for 12 h, and keep warm at 150°C for 24 h to obtain powder;
[0068] S3: 12 g of the powder was mixed with 10 g of polyacrylamide and dissolved in 10 mL of dimethyl sulfoxide. Then 0.08 g of azobisisobutyronitrile was added and heated at 80° C. for 6 h to obtain a composite adhesive.
[0069] This embodiment discloses a method for preparing a ring-shaped NdFeB magnet, comprising the following steps:
[0070] Step 1: 3 kg of NdFeB magnet raw material, 25 g of modified lubricant and 200 mL of distilled water were mixed for 5 hours, smelted, hydrogen crushed and jet milled to obtain NdFeB magnet powder with uniform particle size distribution;
[0071] Step 2: Mix 3kg of NdFeB magnet powder with 250g of composite binder, stir, put into a ring-shaped mold, and press the powder into a ring-shaped green body;
[0072] Step 3: placing the annular green body into a sintering furnace and sintering at high temperature to obtain a magnet;
[0073] Step 4: Grind, cut and nickel-plate the magnet to obtain a ring-shaped NdFeB magnet.
[0074] Example 4: This example discloses a method for preparing a modified lubricant, comprising the following steps:
[0075] Q1: 4.3 g of 3-nitro-1,8-naphthalene dicarboxylic anhydride was added to a container containing 120 mL of anhydrous ethanol, followed by the addition of 1.55 g of N,N-dimethylethylenediamine and 66 mL of 70% by volume ethanol solution. The mixture was heated in an oil bath at 80°C for 4 h under nitrogen protection. After the reaction was completed, the mixture was cooled with ice water, filtered under reduced pressure, washed with n-heptane for 3 times, and dried to obtain an intermediate product 1.
[0076] Q2: 4.5 g of intermediate product 1 was added to a container containing 45 mL of anhydrous ethanol, followed by 2.57 mL of triethylamine and 0.45 g of palladium carbon. Under nitrogen protection, the mixture was heated to reflux at 80 °C with stirring for 8 h, and then 1.2 mL of formic acid was added dropwise to the container through a syringe to initiate the reaction. After the reaction was completed, the mixture was filtered with diatomaceous earth, the filtrate was cooled in ice water, filtered under reduced pressure, washed 3 times with n-heptane, and dried to obtain intermediate product 2;
[0077] Q3: 0.35 g of intermediate product 2, 28 mL of toluene, 1.6 g of 2-methylbenzaldehyde and 0.19 g of diethyl phosphite were added to the container in sequence. Under nitrogen protection, the mixture was stirred and refluxed for 12 h. After the reflux, the mixture was evaporated under reduced pressure and redissolved with dichloromethane. A mixed solution of ethyl acetate and petroleum ether in a volume ratio of 4:1 was used as an eluent for purification to obtain a modified lubricant.
[0078] This embodiment discloses a method for preparing a composite adhesive, comprising the following steps:
[0079] S1: Add 2.5 g of phenolphthalein monomer to a container containing 70 mL of acetic acid, stir to dissolve, then add 2.8 g of yttrium nitrate hexahydrate, stir vigorously for 2 h, pour into a container filled with low-temperature deionized water, wash, filter, and dry to obtain dinitrophenolphthalein; add 6 g of dinitrophenolphthalein to a container containing 40 mL of tetrahydrofuran, stir for 30 min, add 25 mL of anhydrous ethanol and 0.6 g of palladium carbon, evacuate, heat at 70°C for reaction for 12 h, filter after the reaction, heat, cool at 6°C for 10 h, filter, and dry to obtain diaminophenolphthalein;
[0080] S2: Add 5.6g of diaminophenolphthalein to a container, then add 20mL of N-methylpyrrolidone, stir for 45min under a nitrogen atmosphere until completely dissolved, then place in an ice water environment at 0°C, add a total of 6.2g of hexafluorodianhydride three times on average, add once every 20min, stir and react for 24h to obtain mucus; remove the ice water bath, add 17mL of toluene to 21.5mL of mucus, mix well, connect the water separator and condenser to the container, heat at 180°C for 8h, cool naturally, crush, filter, wash and dry the obtained precipitate, and the drying process is: keep warm at 60°C for 24h, keep warm at 90°C for 12h, keep warm at 120°C for 12h, and keep warm at 150°C for 24h to obtain powder;
[0081] S3: 8 g of the powder was mixed with 7 g of polyacrylamide and dissolved in 6 mL of dimethyl sulfoxide. Then 0.06 g of azobisisobutyronitrile was added and heated at 80° C. for 6 h to obtain a composite adhesive.
[0082] This embodiment discloses a method for preparing a ring-shaped NdFeB magnet, comprising the following steps:
[0083] Step 1: 1.5 kg of NdFeB magnet raw material, 22 g of modified lubricant and 220 mL of distilled water were mixed for 5 hours, smelted, hydrogen crushed and jet milled to obtain NdFeB magnet powder with uniform particle size distribution;
[0084] Step 2: Mix 1.5 kg of NdFeB magnet powder with 230 g of composite binder, stir, put into a ring-shaped mold, and press the powder into a ring-shaped green body;
[0085] Step 3: placing the annular green body into a sintering furnace and sintering at high temperature to obtain a magnet;
[0086] Step 4: Grind, cut and nickel-plate the magnet to obtain a ring-shaped NdFeB magnet.
[0087] Example 5: This example discloses a method for preparing a modified lubricant, comprising the following steps:
[0088] Q1: 5.58 g of 3-nitro-1,8-naphthalene dicarboxylic anhydride was added to a container containing 150 mL of anhydrous ethanol, followed by the addition of 2.01 g of N,N-dimethylethylenediamine and 51.2 mL of 70% by volume ethanol solution. The mixture was heated in an oil bath at 80°C for 4 h under nitrogen protection. After the reaction was completed, the mixture was cooled with ice water, filtered under reduced pressure, washed with n-heptane for 3 times, and dried to obtain an intermediate product 1.
[0089] Q2: 5.5 g of intermediate product 1 was added to a container containing 55 mL of anhydrous ethanol, followed by 3.24 mL of triethylamine and 0.55 g of palladium carbon. Under nitrogen protection, the mixture was heated at 80 °C for reflux with stirring for 8 h. Then, 1.4 mL of formic acid was added dropwise to the container through a syringe to initiate the reaction. After the reaction was completed, the mixture was filtered with diatomaceous earth, the filtrate was cooled in ice water, filtered under reduced pressure, washed 3 times with n-heptane, and dried to obtain intermediate product 2;
[0090] Q3: 0.49 g of intermediate product 2, 42 mL of toluene, 2.2 g of 2-methylbenzaldehyde and 0.25 g of diethyl phosphite were added to the container in sequence. Under nitrogen protection, the mixture was stirred and refluxed for 12 h. After the reflux, the mixture was evaporated under reduced pressure and redissolved with dichloromethane. A mixed solution of ethyl acetate and petroleum ether in a volume ratio of 4:1 was used as an eluent for purification to obtain a modified lubricant.
[0091] This embodiment discloses a method for preparing a composite adhesive, comprising the following steps:
[0092] S1: Add 3.2 g of phenolphthalein monomer to a container containing 110 mL of acetic acid, stir to dissolve, then add 4.2 g of yttrium nitrate hexahydrate, stir vigorously for 2 h, pour into a container filled with low-temperature deionized water, wash, filter, and dry to obtain dinitrophenolphthalein; add 9 g of dinitrophenolphthalein to a container containing 50 mL of tetrahydrofuran, stir for 30 min, add 35 mL of anhydrous ethanol and 0.9 g of palladium carbon, evacuate, heat at 70°C for reaction for 12 h, filter after the reaction, heat, cool at 6°C for 10 h, filter, and dry to obtain diaminophenolphthalein;
[0093] S2: Add 7.3g of diaminophenolphthalein to a container, then add 22mL of N-methylpyrrolidone, stir for 45min under nitrogen atmosphere until completely dissolved, then place in an ice water environment at 0°C, add a total of 8.7g of hexafluorodianhydride three times on average, add once every 20min, stir and react for 24h to obtain mucus; remove the ice water bath, add 16mL of toluene to 20.5mL of mucus, mix well, connect the water separator and condenser to the container, heat at 180°C for 8h, cool naturally, crush, filter, wash and dry the obtained precipitate, and the drying process is: keep warm at 60°C for 24h, keep warm at 90°C for 12h, keep warm at 120°C for 12h, and keep warm at 150°C for 24h to obtain powder;
[0094] S3: 11 g of the powder was mixed with 9 g of polyacrylamide and dissolved in 9 mL of dimethyl sulfoxide. Then 0.07 g of azobisisobutyronitrile was added and heated at 80° C. for 6 h to obtain a composite adhesive.
[0095] This embodiment discloses a method for preparing a ring-shaped NdFeB magnet, comprising the following steps:
[0096] Step 1: Mix 2.5 kg of NdFeB magnet raw material, 24 g of modified lubricant and 260 mL of distilled water for 5 hours, smelt, hydrogen crush and jet mill to obtain NdFeB magnet powder with uniform particle size distribution;
[0097] Step 2: Mix 2.2 kg of NdFeB magnet powder with 220 g of composite binder, stir, put into a ring-shaped mold, and press the powder into a ring-shaped green body;
[0098] Step 3: placing the annular green body into a sintering furnace and sintering at high temperature to obtain a magnet;
[0099] Step 4: Grind, cut and nickel-plate the magnet to obtain a ring-shaped NdFeB magnet.
[0100] Comparative Example 1
[0101] Comparative Example 1 Compared with Example 1, in the preparation process of the modified lubricant in Comparative Example 1, 3-nitro-1,8-naphthalene dicarboxylic anhydride was not added, and other conditions remained unchanged.
[0102] Comparative Example 2
[0103] Comparative Example 2 Compared with Example 1, in the preparation process of the composite binder in Comparative Example 2, hexafluorodianhydride is not added, and other conditions remain unchanged.
[0104] Comparative Example 3
[0105] Comparative Example 3 Compared with Example 1, in the preparation process of the annular NdFeB magnet in Comparative Example 3, no modified lubricant is added, and other conditions remain unchanged.
[0106] Comparative Example 4
[0107] Comparative Example 4 Compared with Example 1, in the preparation process of the annular NdFeB magnet in Comparative Example 4, no composite binder is added, and other conditions remain unchanged.
[0108] The obtained samples were subjected to density test, and then the remanence and intrinsic coercivity of the samples were tested according to GB / T 24270-2009. The test results are shown in Table 1:
[0109] Table 1
[0110]
[0111]
[0112] From the test results in Table 1, it can be seen that the magnets prepared in Examples 1-5 of the present invention have high density and excellent magnetic properties. From the comparison between Comparative Example 1 and Examples 1-5, it can be seen that the addition of 3-nitro-1,8-naphthalene dicarboxylic anhydride can make the magnet have excellent magnetic properties; from the comparison between Comparative Example 2 and Examples 1-5, it can be seen that the addition of hexafluorodianhydride can make the magnet have excellent density and magnetic properties; from the comparison between Comparative Example 3 and Examples 1-5, it can be seen that the addition of modified lubricants can make the magnet have excellent magnetic properties; from the comparison between Comparative Example 4 and Examples 1-5, it can be seen that the addition of composite binders can make the magnet have excellent density and magnetic properties.
[0113] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0114] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a ring-shaped NdFeB magnet, characterized in that: The following steps are involved: Step 1: Mixing NdFeB magnet raw materials, modified lubricant and distilled water, smelting, hydrogen crushing and jet milling to obtain NdFeB magnet powder with uniform particle size distribution; Step 2: Mix the NdFeB magnet powder with the composite binder, stir, put into a mold, and press the powder into a ring-shaped green body; Step 3: placing the annular green body into a sintering furnace and sintering at high temperature to obtain a magnet; Step 4: Grind, cut and nickel-plate the magnet to obtain a ring-shaped NdFeB magnet.
2. The method for preparing a ring-shaped NdFeB magnet according to claim 1, characterized in that: In the step 1, the dosage ratio of the NdFeB magnet raw material, the modified lubricant and the distilled water is (1-3) kg: (20-25) g: (200-280) mL, and the mixing time is 4-5 h.
3. The method for preparing a ring-shaped NdFeB magnet according to claim 1, characterized in that: The preparation method of the modified lubricant comprises the following steps: Q1: Add 3-nitro-1,8-naphthalene dicarboxylic anhydride to a container containing anhydrous ethanol, then add N,N-dimethylethylenediamine and ethanol solution, and heat the reaction in an oil bath under nitrogen protection. After the reaction is completed, cool with ice water, filter under reduced pressure, wash, and dry to obtain intermediate 1; Q2: Add the intermediate product 1 to a container containing anhydrous ethanol, then add triethylamine and palladium carbon, heat under reflux and stir under nitrogen protection, then add formic acid dropwise into the container through a syringe to initiate the reaction, filter after the reaction, cool the filtrate in ice water, filter under reduced pressure, wash, and dry to obtain the intermediate product 2; Q3: The intermediate product 2, toluene, 2-methylbenzaldehyde and diethyl phosphite are added into the container in sequence, and refluxed with stirring under nitrogen protection. After the reflux is completed, the mixture is evaporated under reduced pressure, redissolved and purified to obtain a modified lubricant.
4. The method for preparing a ring-shaped NdFeB magnet according to claim 3, characterized in that: In Q1, the dosage ratio of 3-nitro-1,8-naphthalene dicarboxylic anhydride, anhydrous ethanol, N,N-dimethylethylenediamine and ethanol solution is (3.66-6.22) g: (100-170) mL: (1.32-2.24) g: (45-76.5) mL, the volume fraction of the ethanol solution is 70 vt%, the oil bath heating reaction temperature is 70-80°C, the reaction time is 2-4 h, and the reaction is washed 3-5 times with n-heptane.
5. The method for preparing a ring-shaped NdFeB magnet according to claim 3, characterized in that: In Q2, the usage ratio of the intermediate product 1, anhydrous ethanol, triethylamine, palladium carbon and formic acid is (4-6) g: (40-60) mL: (2.3-3.45) mL: (0.4-0.6) g: (1-1.5) mL, the heating reflux stirring temperature is 70-90°C, the time is 6-8h, filtered with diatomaceous earth, and washed with n-heptane 3-5 times.
6. The method for preparing a ring-shaped NdFeB magnet according to claim 3, characterized in that: In Q3, the dosage ratio of the intermediate product 2, toluene, 2-methylbenzaldehyde and diethyl phosphite is (0.28-0.56) g: (25-50) mL: (1.2-2.4) g: (0.14-0.28) g, the stirring reflux time is 10-12 h, redissolved with dichloromethane, and purified using a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 4:1 as an eluent.
7. The method for preparing a ring-shaped NdFeB magnet according to claim 1, characterized in that: In the step 2, the ratio of NdFeB magnet powder to composite binder is (1-3) kg: (200-250) g, and the mold used is a circular ring mold.
8. The method for preparing a ring-shaped NdFeB magnet according to claim 1, characterized in that: The preparation method of the composite binder comprises the following steps: S1: Add phenolphthalein monomer to a container containing acetic acid, stir to dissolve, then add yttrium nitrate hexahydrate, stir vigorously, pour into a container filled with low-temperature deionized water, wash, filter, and dry to obtain dinitrophenolphthalein; add dinitrophenolphthalein to a container containing tetrahydrofuran, stir, add anhydrous ethanol and palladium carbon, evacuate, heat to react, filter after the reaction is completed, heat, cool, filter, and dry to obtain diaminophenolphthalein; S2: Add diaminophenolphthalein to a container, then add N-methylpyrrolidone, stir until completely dissolved under a nitrogen atmosphere, then place in an ice-water environment, add hexafluorodianhydride in portions, stir to react, and obtain a mucus; remove the ice-water bath, add toluene to the mucus, mix well, connect a water separator and a condenser to the container, heat to react, cool naturally, and crush, filter, wash, and dry the obtained precipitate to obtain a powder; S3: The powder is mixed with polyacrylamide and dissolved in dimethyl sulfoxide, and then azobisisobutyronitrile is added, and heated to react to obtain a composite adhesive.
9. The method for preparing a ring-shaped NdFeB magnet according to claim 8, characterized in that: In S1, the amount ratio of phenolphthalein monomer, acetic acid and yttrium nitrate hexahydrate is (2-4) g: (60-120) mL: (2.4-4.8) g, and the vigorous stirring time is 1-2 h; the amount ratio of dinitrophenolphthalein, tetrahydrofuran, anhydrous ethanol and palladium carbon is (5-10) g: (30-60) mL: (20-40) mL: (0.5-1) g, the stirring time is 20-30 min, the heating reaction temperature is 60-70° C., the time is 10-12 h, and the cooling temperature is 3-6° C., and the time is 10-14 h; in S2, diaminophenolphthalein, N-methylpyrrolidine The dosage ratio of ketone and hexafluorodianhydride is (4.2-8.4) g: (15-30) mL: (5.3-10.6) g, the stirring time is 30-45 min, the time in the ice water environment is 0-3°C, the time interval for adding hexafluorodianhydride is 20-25 min, and the stirring reaction time is 20-24 h; the dosage ratio of mucus and toluene is (20-22) mL: (15-18) mL, the heating reaction temperature is 160-180°C, the time is 6-8 h, and the drying process is: keep warm at 60°C for 24 h, keep warm at 90°C for 12 h, keep warm at 120°C for 12 h, and keep warm at 150°C for 24 h.
10. The method for preparing a ring-shaped NdFeB magnet according to claim 8, characterized in that: In the S3, the usage ratio of powder, polyacrylamide, dimethyl sulfoxide and azobisisobutyronitrile is (7-12) g: (6-10) g: (5-10) mL: (0.05-0.08) g, the heating reaction temperature is 70-80° C., and the time is 5-7 h.
Citation Information
Patent Citations
Production method of circular-ring-shaped neodymium-iron-boron magnet
CN111968817A
Cited By
Casting waste sand based compression-resistant reclaimed sand and preparation method thereof
CN120170025A